Method for preparing positive electrode active material for rechargeable battery
Patent Information
- Application Number
- JP2023537158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-18
- Filing Date
- 2021-12-17
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-12-17
Smart Images

Figure 0007641384000006 
Figure 0007641384000007 
Figure 0007641384000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a positive electrode active material for a solid-state rechargeable battery (SSB). [Background technology]
[0002] SSBs typically comprise a negative electrode (anode), an electrolyte, and a positive electrode (cathode) that contains lithium in the form of a lithium transition metal oxide. Particularly noteworthy classes of transition metal oxides include nickel-manganese-cobalt (NMC) oxide and nickel-cobalt-aluminium (NCA) oxide. However, the applicability of these materials is limited due to the limited capacity retention of the materials after repeated charge-discharge cycles at higher temperatures and higher voltages.
[0003] Therefore, new materials containing small amounts of Li-W compounds are being developed. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides improved stability and electrochemical properties, such as lower capacitance leakage (Q total ), in particular a Q of less than 55 mAh / g at a temperature of 80° C., as evaluated according to the test method specified below. total The present invention aims to provide a method for producing a positive electrode active material having the above structure. [Means for solving the problem]
[0005] The present invention relates to a method for producing a cathode active material for an SSB, in particular for a cathode active material for a solid-state rechargeable battery comprising Li, O and M, wherein M is Co with a content x of 0 mol% or more and 35.00 mol% or less; Mn with a content y of 0 mol% or more and 35.00 mol% or less; A having a content z of 0 mol% or more and 10.00 mol% or less, which is at least one element selected from B, Mg, Al, Nb, Ti, W, Y, Ca, S, P, Sn, Si and Zr; and Ni with a content of 100.00mol%-xyz It consists of: The present invention provides a solution to at least one of the above problems by providing a method, in which the contents x, y and z are relative to M and are determined by ICP.
[0006] The inventors have found that the positive electrode active material prepared by the method according to the present invention has a lower capacity leakage (Q total ) was found to be exhibited.
[0007] For further guidance and to better understand the teachings of the present invention, the drawings are included, which are intended to aid in the explanation of the invention and are not intended to limit the invention disclosed herein.
[0008] The figures and symbols contained therein have meanings commonly understood by one of ordinary skill in the art to which this invention pertains. [Brief description of the drawings]
[0009] [Figure 1A] 1 shows an SEM image of a particle having the formula Li1.01(Ni0.63Mn0.22Co0.15)0.99O2. [Figure 1B] 1 shows an SEM image of the same material with Li6W2O9 deposited on the positive electrode active material obtained by the method according to the present invention. [Diagram 2] X-ray diffractograms of EX1.1, CEX1 and Li6W2O9 secondary phases are shown. [Diagram 3] TEM / EDS line profiling of a cross section of EX1.1 produced by SEM-FIB is shown. [Figure 4]The full cell cycling performance of EX1.1 and CEX1 is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by one of ordinary skill in the art to which this invention belongs. By way of further guidance, definitions of terms are included to better understand the teachings of the present invention.
[0011] The recitation of numerical ranges by endpoints includes not only the recited endpoints but also all numbers and fractions subsumed within that range. All percentages are understood to be percent by weight, abbreviated as "wt. %," unless otherwise defined or a different meaning is apparent to one of ordinary skill in the art from its use and the context in which it is used.
[0012] When an element or component is stated to be present in a content of 0% or more or ≧0, this is intended to mean that the presence of this element or component is optional.
[0013] In a first aspect, the present invention relates to a method for producing a cathode active material for a solid state rechargeable battery, the active material comprising Li, O and M, M consisting of Co with a content x of 0 mol% or more and 35.00 mol% or less, Mn with a content y of 0 mol% or more and 35.00 mol% or less, A with a content z of 0 mol% or more and 10.00 mol% or less, A being at least one element selected from B, Mg, Al, Nb, Ti, W, Y, Ca, S, P, Sn, Si and Zr, and Ni with a content of 100.00 mol%-xyz, the contents x, y and z being relative to M and determined by ICP, the method comprising the steps of: Step 1: preparing a slurry, the slurry comprising a liquid and a lithium mixed metal oxide powder, the lithium mixed metal oxide powder comprising Li, O and Q, Q being Co with a content a of 0 mol% or more and 35.00 mol% or less, Mn with a content b of 0 mol% or more and 35.00 mol% or less, G with a content c of 0 mol% or more and 10.00 mol% or less, the G being at least one element selected from B, Mg, Al, Nb, Ti, W, Y, Ca, S, P, Sn, Si and Zr, and Ni with a content of 100.00 mol%-abc, the contents a, b and c being relative to M and determined by ICP; Step 2: The lithium mixed metal oxide powder is treated with Al before and / or after and / or during step 1. 3+ , La 3+ , Co 2+ , Co 3+ , Mn 2+ , Mn 3+ , Mn 4+ , Mn 6+ , Zn 2+ , Cu + , Cu 2+ , Mg 2+ and a cation precursor comprising at least one cation selected from the general formula A' y’ O z’ -x’ with an anion precursor comprising at least one anion having the formula: (wherein A' is selected from B, Al, Sn, Si, P, W, and 0.5≦x'≦4, 0.5≦y'≦2, and 1≦z'≦12); Step 3: Optionally, filtering and optionally drying the slurry to obtain a wet or dry solid fraction; Step 4: Heating the slurry from steps 1 and 2 or the solid fraction from step 3 at a temperature in the range of 300°C to 1000°C.
[0014] In the context of the present invention, the terms "cation precursor" and "anion precursor" are to be understood as compounds which, when dissolved in the liquid, give rise to cations or anions, respectively. Preferably, the cation precursor and the anion precursor are quantitatively, i.e. more than 99%, soluble when added to water. Examples of cation precursors and anion precursors are shown in Table 1.
[0015] In a preferred embodiment, the positive electrode active material has a Li / (Ni+Co+Mn) molar ratio of 0.90 or greater and 1.10 or less, and the lithium mixed metal oxide powder has a Li / (Ni+Co+Mn) molar ratio of 0.90 or greater and 1.10 or less.
[0016] Preferably, the liquid is water.
[0017] According to such a method, an additional phase can be easily introduced, thereby increasing the Q of the resulting positive electrode active material. total will improve.
[0018] Preferably, but not necessarily, step 3 is present.
[0019] In a preferred embodiment, the temperature in step 4 is 350°C to 1000°C, preferably 350°C to 800°C.
[0020] In a preferred embodiment, x is 2.0 mol % or more, more preferably 5.0 mol % or more.
[0021] In a preferred embodiment, a is 2.0 mol % or more, more preferably 5.0 mol % or more.
[0022] The inventors have found that further heat treatment at temperatures above 300°C increases the Q total It has been found that the temperature is reduced, indicating a reduction in volume leakage. Preferably, the temperature is greater than 350°C, greater than 400°C, or even greater than 450°C.
[0023] Preferably, the temperature is less than 900° C., or even less than 800° C. Most preferably, the temperature is about 350° C., 400° C., 450° C., 500° C., 550° C., 600° C., 650° C., 700° C., or 750° C., or any temperature therebetween. Preferably, the duration of step 4) is 1 hour or more, more preferably 2 hours or more. Preferably, the duration of step 4) is 24 hours or less, more preferably 12 hours or less.
[0024] In a preferred embodiment, the lithium mixed metal oxide powder is a single crystal powder, in other words, a plurality of single crystal particles.
[0025] The concept of single crystal powder is well known in the art of cathode active materials. It relates to powders with predominantly single crystalline particles. Such powders are a separate type of powder compared to polycrystalline powders made from particles that are predominantly polycrystalline. Those skilled in the art can easily distinguish between these two types of powders based on microscopic images.
[0026] Single crystal particles are also known in the art as monolithic particles, integral particles or / and single crystalline particles.
[0027] Even if a technical definition of a single crystal powder is unnecessary, since such powders can be easily recognized by one skilled in the art using an SEM, in the context of the present invention, a single crystal powder can be considered to be defined as a powder in which 80% or more of the particles by number are single crystal particles. This means a particle size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm). 2 ), preferably at least 100 μm×100 μm (i.e., at least 10,000 μm 2 ) on an SEM image with a field of view.
[0028] A monocrystalline particle is a particle that is an individual crystal or is formed from fewer than five, preferably at most three, primary particles that are themselves individual crystals, which can be observed by observing the grain boundaries with a suitable microscopic technique such as a Scanning Electron Microscope (SEM).
[0029] When determining whether a particle is a single crystal particle, grains having a maximum linear dimension observed by SEM that is less than 20% of the median particle size D50 of the powder as determined by laser diffraction are ignored. This avoids particles that are essentially single crystal but may have several very small other grains deposited on them, e.g., a polycrystalline coating, being inadvertently considered not to be single crystal particles.
[0030] Preferably, the cathode active material comprises Li, O and Q, Q being composed of Co with a content a of 5.0 mol% or more and 35.00 mol% or less, Mn with a content b of 0 mol% or more and 35.00 mol% or less, G with a content c of 0 mol% or more and 10.00 mol% or less, G being at least one element selected from B, Mg, Al, Nb, Ti, W, Y, Ca, S, P and Zr, and Ni with a content of 100.00 mol%-abc, the contents a, b and c being the contents relative to Q and determined by ICP, and the lithium mixed metal oxide powder has a Li / (Ni+Co+Mn) molar ratio of 0.90 or more and 1.10 or less.
[0031] Preferably, the positive electrode active material is a powder and has a median particle size of 2 μm to 15 μm, more preferably a median particle size of 3 μm to 12 μm, most preferably a median particle size of 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or any value therebetween, as determined by laser diffraction granulometry. The median particle size (D50) of the compound is obtained by laser diffraction granulometry. The laser particle size distribution is measured using a Malvern Mastersizer 2000 equipped with a Hydro 2000MU wet dispersion accessory after dispersing the powder in an aqueous medium. To improve the dispersion of the powder in the aqueous medium, sufficient ultrasonic irradiation (typically 1 minute for 12 ultrasonic displacements) and stirring are applied, and a suitable surfactant is introduced.
[0032] Preferably, the cation precursor comprises a sulfate, nitrate, carbonate, hydroxide, oxyhydroxide, acetate, phosphate, borate, and mixtures thereof of the cation, more preferably, the cation precursor comprises a sulfate and / or a nitrate.
[0033] Preferably, the anion precursor is AlO2 - , WO4 2- , SiO3 2- , PO4 3- , BO3 3- , B(OH)4 - , SnO3 2- The anion comprises at least one anion selected from the group consisting of
[0034] Preferably, the present invention relates to an anion precursor having the general formula Na x’ A' y’ O z’ The present invention provides a method according to a first aspect of the present invention, comprising:
[0035] Preferably, the present invention provides a process according to the first aspect of the invention, wherein the cation precursor is mixed with the lithium mixed metal oxide powder in an amount of 0.2 mol % to 2.0 mol %, preferably 0.4 mol % to 1.5 mol %, more preferably 0.50 mol %, 0.75 mol %, 1.00 mol %, or any value therebetween, based on the total amount of lithium.
[0036] Preferably, the present invention provides a process according to the first aspect of the invention, wherein the anion precursor is mixed with the lithium mixed metal oxide powder in an amount of 0.2 mol % to 2.0 mol %, preferably 0.4 mol % to 1.5 mol %, more preferably 0.50 mol %, 0.75 mol %, 1.00 mol %, or any value therebetween, based on the total amount of lithium.
[0037] Preferably, the invention provides a process according to the first aspect of the invention, wherein the cation and anion precursors are mixed in step 2 in stoichiometrically equivalent amounts.
[0038] Preferably, the cation and anion precursors form a water-insoluble salt.
[0039] In other words, preferably after steps 1 and 2, a precipitate of the cations and the anions is formed.
[0040] Preferably, after addition of the cation and anion precursors, the slurry is stirred at a temperature between 15°C and 100°C, more preferably between 25°C and 80°C, and most preferably at a temperature of about 40°C, 50°C, 60°C, 70°C or any value therebetween.
[0041] Preferably, the slurry is an aqueous slurry.
[0042] Preferably, the cation precursor and the anion precursor are soluble in the liquid.
[0043] Preferably, the positive electrode active material comprises a phase, as determined by XRD, that corresponds to a crystalline salt of lithium ions and the anion.
[0044] Preferably, A' is the element W.
[0045] Preferably, the cation precursor is Co 2+ and / or Co. 3+ Includes.
[0046] Preferably, A' is the element W and the positive electrode active material comprises Li6W2O9 as determined by XRD.
[0047] Preferably, x≦15.00 mol % and y≦1.00 mol %, A comprises Al, and M has an Al content of 1.00 mol % or more.
[0048] Preferably, z≦5.00 mol % and 10.00 mol %≦y.
[0049] Preferably, 15.00 mol%≦x≦30.00 mol%, 15.00 mol%≦y≦30.00 mol%, and z≦3.00 mol%.
[0050] Preferably, the positive electrode active material powder is a plurality of particles, and the particles are single crystal particles. When determining whether a particle is a single crystal particle, the phase containing the anion is excluded from consideration.
[0051] In a second aspect, the present invention provides a cathode active material for a solid-state rechargeable battery, obtained by the method according to the first aspect of the present invention. The inventors have found that the cathode active material prepared by the method according to the present invention has a lower capacity leakage (Q total ) was found to be exhibited.
[0052] In a third aspect, the present invention provides a cathode active material for a rechargeable solid-state battery, the cathode active material being a powder, the cathode active material having a Co content of Co A , Ni content Ni A , and Mn content Mn A Co A , Ni A and Mn A was determined by ICP analysis, and Co A , Ni A and Mn A is expressed as mole percent, and the positive electrode active material is Co A / (Co A +Ni A +Mn A) and the powder has an average Co fraction Co as measured by XPS analysis. B , average Ni fraction Ni B and the average Mn fraction Mn B indicates Co B , Ni B and Mn B is expressed as mole percent, and the positive electrode active material is Co B / (Co B +Ni B +Mn B ) and the positive electrode active material has a value B defined as Li x W y O z phase, 1.0≦x≦8.0, 1.0≦y≦5.0, 3.0≦z≦10.0, and the ratio B / A is at least 1.25.
[0053] where Co A , Ni A , Mn A , Co B , Ni B and Mn B Each of is greater than or equal to 0%.
[0054] In a preferred embodiment of the third aspect, the active cathode material is a Li-containing active cathode material for a Li-ion rechargeable solid-state battery. In a preferred embodiment of the third aspect, the active cathode material has a Li content, Li, determined by ICP and expressed as a mole fraction. A Li A / (Co A +Ni A +Mn A ) is at least 0.81 and at most 1.21, preferably Li A / (Co A +Ni A +Mn A ) is higher than 0.95.
[0055] In a preferred embodiment of the third aspect, the Li x W y O z The phase is Li6W2O9 as determined by XRD.
[0056] In a preferred embodiment of the third aspect, the Li6W2O9 has a Pm3m crystal structure as determined by XRD.
[0057] In a preferred embodiment of the third aspect, the Li x W y O z The phase is preferably present as secondary particles on the surface of the particle as determined by TEM-EDS.
[0058] In a preferred embodiment of the third aspect, the positive electrode active material is Co A and Ni A and Mn A and a W content of at least 0.1 mol % of the sum of the above.
[0059] In a preferred embodiment of the third aspect, the positive electrode active material is Co A and Ni A and Mn A The sum of these is at most 2.0 mol %, preferably Co. A and Ni A and Mn A The total of the W content is at most 1.0 mol %.
[0060] In a preferred embodiment of the third aspect, the ratio B / A is at least 1.5, preferably at least 2.0.
[0061] In a preferred embodiment of the third aspect, the cathode active material is producible or produced by a method according to the first aspect of the invention or a preferred variant thereof.
[0062] In a preferred embodiment of the third aspect, the ratio B / A is at most 4.0, preferably at most 2.5.
[0063] In a preferred embodiment of the third aspect, the powder is a single crystal powder.
[0064] In a preferred embodiment of the third aspect, Ni A / (Co A +Ni A +Mn A ) is at least 0.35, preferably at least 0.55.
[0065] In a preferred embodiment of the third aspect, Co A / (Co A +Ni A +Mn A ) is at least 0.02 and at most 0.40.
[0066] In a preferred embodiment of the third aspect, the powder has a particle size distribution determined by laser diffraction, the particle size distribution having a median particle size D50 of at least 1.0 μm and at most 15 μm.
[0067] In a preferred embodiment of the third aspect, the positive electrode active material has a content X of one or more elements X. A X is one or more of B, Mg, Al, Nb, Ti, and Zr; A is determined by ICP, and X A is expressed as a mole fraction, Mn A / (Co A +Ni A +Mn A ) is at least 0.10 and at most 0.60, and Co A / (Co A +Ni A +Mn A ) is at least 0.02 and at most 0.40, and X A / (Co A +Ni A +Mn A ) is at most 0.10, and Ni A / (Co A +Ni A +Mn A ) is at most 0.88. EXAMPLES
[0068] The following examples are intended to further clarify the invention, but are not intended to limit the scope of the invention. Please note that Examples 1 to 8 relate to examples of the method according to the invention as defined in claim 1, and Example 1 relates to an example of the product according to the invention as defined in claim 14.
[0069] 1. Description of analysis method 1.1.SEM (Scanning Electron Microscope) Analysis The morphology of the positive electrode active material is analyzed by scanning electron microscopy (SEM) technique. This measurement is 9.6×10 -5 This is performed using a JEOL JSM7100F under a high vacuum environment of 100 Pa.
[0070] 1.2. Inductively Coupled Plasma The composition of the positive electrode active material powder is measured by an inductively coupled plasma (ICP) method using an Agilent 720 ICP-OES (Agilent Technologies, https: / / www.agilent.com / cs / library / brochures / 5990-6497EN%20720-725_ICP-OES_LR.pdf). One gram of powder sample is dissolved in 50 mL of high-purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with a watch glass and heated on a hot plate at 380 °C until the powder is completely dissolved. After cooling to room temperature, the solution from the Erlenmeyer flask is poured into a first 250 mL volumetric flask.
[0071] The first volumetric flask is then filled with deionized water up to the 250 mL mark, followed by a complete homogenization process (first dilution). An appropriate amount of solution is removed from the first volumetric flask with a pipette and transferred to a second 250 mL volumetric flask for the second dilution, and the second volumetric flask is filled to the 250 mL mark with internal standard elements and 10% hydrochloric acid, followed by homogenization. Finally, this solution is used for ICP measurement.
[0072] The results of the ICP measurements are calculated and expressed as fractions, which are the molar contents of the elements compared to the total molar contents of Ni, Co and Mn.
[0073] 1.3.Coin Cell 1.3.1. Preparation of Coin Cells In preparing the positive electrode, the positive electrode active material powder and the conductor (SuperP, Timcal (Imerys Graphite & Carbon), http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2018 / 10 / ENSACO-1 50-210-240-250-260-350-360-G-ENSACO- A slurry containing 150-250-P-SUPER-P-SUPER-P-Li-C-NERGY-SUPER-C-45-65-T_V-2.2_-USA-SDS.pdf), binder (KF#9305, Kureha, http: / / www.kureha.co.jp / en / business / material / pdf / KFpolymer_BD_en.pdf) (90:5:5 by weight), and solvent (NMP, Mitsubishi, https: / / www.m-chemical.co.jp / en / products / departments / mcc / c4 / product / 1201005_7922.html) is prepared by using a high-speed homogenizer. The homogenized slurry is spread on one side of an aluminum foil using a doctor blade coater with a gap of 230 μm. The foil coated with the slurry is dried in an oven at 120° C. and then pressed using a calendaring tool. It is then dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard® 2320, Arora, P. & Zhang, Z. (John) (2004) Battery Separators. Chemical Reviews, 104(10), 4419-4462) is placed between the positive electrode and a piece of lithium foil used as the negative electrode. 1M LiPF6 in EC:DMC (1:2 by volume) is used as the electrolyte solution and dropped between the separator and the electrode. The coin cell is then completely sealed to prevent electrolyte leakage.
[0074] Test Method Each coin cell is cycled at 25 °C using a Toscat-3100 computer-controlled constant current cycling station (Toyo System, http: / / www.toyosystem.com / image / menu3 / toscat / TOSCAT-3100.pdf). The coin cell test procedure uses a 1C current definition of 160 mA / g in the 4.3-3.0 V / Li metal window range according to Table 1. The initial charge capacity (CQ1) and discharge capacity (DQ1) are measured in constant current mode (CC) at a C-rate of 0.1 C. The irreversible capacity IRRQ is expressed in % as follows: IRRQ(%)=100×(CQ1-DQ1) / CQ1
[0075] [Table 1]
[0076] 1.4.Full Cell 1.4.1. Preparation of full cells A 200 mAh pouch-type cell is prepared as follows: positive electrode active material powder, Super-P as a positive electrode conductive agent (Super-P, Timcal, (Imerys Graphite&Carbon), http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2018 / 10 / ENSACO-150-210-240-250-260-350-360-G-ENSACO-150-250-P-SUPER-P-SUPER-P-Li-C-NERGY-SUPER-C-45-65-T_V-2.2_-USA-SDS.pdf), graphite (KS-6, Timrex (Imerys Graphite&Carbon, http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2014 / 04 / Powder-Metallurgy.pdf), and polyvinylidene fluoride (PVDF 1710, Kureha, https: / / www.kureha.co.jp / en / business / material / pdf / KFpolymer_BD_en.pdf) as a positive electrode binder, N-methyl-2-pyrrolidone (NMP) as a dispersion medium, positive electrode active material powder, positive electrode conductive agent: super The mass ratio of P, graphite, and the positive electrode binder was 92 / 3 / 1 / 4. The mixture was then kneaded to prepare a positive electrode mixed slurry. The resulting positive electrode mixed slurry was then applied to both sides of a positive electrode current collector made of aluminum foil with a thickness of 15 μm. The width of the applied area was 26 mm, and the length was 190 mm. The typical loading weight of the positive electrode active material was about 11±1 mg / cm. 2 The electrode is then dried and calendared using 120 Kgf pressure, and an aluminum plate is arc welded to the end of the positive electrode to act as the positive current collector tab.
[0077] A commercially available anode is used. Briefly, a mixture of artificial graphite, sodium carboxy-methyl-cellulose (CMC), and styrene-butadiene-rubber (SBR) in a mass ratio of 96 / 2 / 2 is applied to both sides of a copper foil. A nickel plate is arc-welded to the end of the anode, which acts as the anode current collector tab. The typical loading of the anode active material is about 9±1 mg / cm. 2 A non-aqueous electrolyte is obtained by dissolving lithium hexafluorophosphate (LiPF6) salt at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. It contains 0.5 wt% lithium bis(oxalato)borate (LiBOB), 0.5 wt% 1,3-propane sultone (PRS), and 1.0 wt% vinylene carbonate (VC) as additives.
[0078] The positive electrode sheet, the negative electrode sheet, and the microporous polymer separator sheet (22 μm) interleaved therebetween are spirally wound using a winding core rod to obtain a spirally wound electrode assembly. The assembly and electrolyte are then placed in an aluminum laminated pouch in an air drying room with a dew point of −50° C., thereby preparing a flat pouch-type lithium rechargeable battery. The design capacity of the rechargeable battery is 200 mAh when charged to 4.20 V. The full cell test procedure uses a 1C current definition of 200 mA / g.
[0079] Test Method A. Pre-charging and formation The prepared dry battery is soaked in the non-aqueous electrolyte solution at room temperature for 8 hours. The battery is precharged to 15% of its theoretical capacity at a current of 0.25C and aged at room temperature for 1 day. Then the battery is degassed at a pressure of -760mmHg for 30 seconds and the aluminum pouch is sealed.
[0080] The battery is charged at a current of 0.25 C in CC mode (constant current) to 4.2 V or 4.3 V and in CV mode (constant voltage) until a cut-off current of C / 120 is reached. The battery is discharged at a current of 0.50 C in CC mode down to 2.7 V. The battery is then fully charged at a current of 0.50 C in CC mode to 4.2 V or 4.3 V and in CV mode until a cut-off current of C / 20 is reached. The charged battery is aged for one week. The aged battery is ready for the final charging and cycling steps.
[0081] B. Final charge The aged battery after the pre-charging and forming steps is discharged at a current of 0.50 C in CC mode down to 2.7 V. It is charged again at a current of 1.0 C in CC mode down to 4.2 V or 4.3 V and in CV mode until a cut-off current of C / 20 is reached. The battery is then discharged at a current of 0.2 C in CC mode down to 2.7 V. The discharge capacity obtained in this discharge step is defined as the specific capacity (SQ) of the battery. The battery is charged at a current of 1.0 C in CC mode down to 4.2 V or 4.3 V. The final charge step is performed at 25° C.
[0082] C. Cycle life test A lithium rechargeable full-cell battery is continuously charged and discharged under the following conditions, all at 25° C., to determine its charge-discharge cycle performance: Charge in CC mode at 1C rate up to 4.2V, then in CV mode until it reaches C / 20. The cell is then allowed to rest for 10 minutes.
[0083] Discharge in CC mode at 1C rate until the voltage drops to 2.7V. The cell is then allowed to rest for 10 minutes. Charge-discharge cycles are performed up to 800 or 1000 cycles. After every 100 cycles, discharge at 0.2C rate in CC mode until the voltage drops to 2.7V.
[0084] The retention capacity at the nth cycle is calculated as the ratio of the discharge capacity obtained at the nth cycle to that at the 1st cycle.
[0085] 1.5.X-ray Diffraction X-ray diffraction patterns of the positive electrode active material are collected using a Rigaku X-ray diffractometer D / max2000 (Rigaku, Du, Y., et al. (2012). A general method for the large-scale synthesis of uniform ultrathin metal sulphide nanocrystals. Nature Communications, 3(1)) with a CuKα radiation source (40 kV, 40 mA) emitting at a wavelength of 1.5418 Å. The instrument configuration is set to a 1° Soller slit (SS), a 10 mm divergent height limiting slit (DHLS), a 1° divergence slit (DS), and a 0.3 mm reception slit (RS). The diameter of the goniometer is 185 mm. For XRD, diffraction patterns are acquired in the range of 15-65° (2θ) with a scan speed of 1° / min and a step size of 0.02° / scan.
[0086] 1.6.X-ray photoelectron spectroscopy In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In XPS measurements, signals are obtained from the first few nanometers (e.g., 1 nm to 10 nm) of the sample surface layer. Therefore, all elements measured by XPS are contained in the surface layer.
[0087] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-α+ spectrometer (Thermo Scientific, https: / / www.thermofisher.com / order / catalog / product / IQLAADGAAFFACVMAHV).
[0088] Monochromatic Al Kα radiation (hυ=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. An extensive survey scan to identify the elements present at the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection.
[0089] At least 10 accurate narrow scans are then performed at 50 eV for each identified element to obtain a high signal-to-noise ratio.
[0090] Curve fitting is performed with CasaXPS version 2.3.19PR1.0 (Casa Software, http: / / www.casaxps.com / ) using Shirley-type background processing and Scofield sensitivity coefficients. Fitting parameters are according to Table 2a. Line shape GL(30) is the Gaussian / Lorentzian product formula at 70% Gaussian and 30% Lorentzian lines. LA(α,β,m) is the asymmetric line shape, where α and β define the tail broadening of the peak and m defines the width.
[0091] [Table 2]
[0092] For the Mn, Co, and W peaks, limits are set for each defined peak according to Table 2b. W atomic ratios are quantified from the W4f7 and W4f5 peaks, and therefore W5p3 is not quantified.
[0093] [Table 3]
[0094] The Co surface content is expressed as the atomic content of Co in the surface layer of a particle divided by the total atomic content of Ni, Mn, and Co in said surface layer.
[0095] 1.7. Transmission Electron MicroscopyEnergy Dispersive X-ray Spectroscopy To investigate the Ni, Mn, Co, and W distribution within the positive electrode active material powder particles, cross-sectional TEM lamellae of the particles are prepared by a Helios Nanolab 450hp dual beam scanning electron microscope-focused ion beam (SEM-FIB) (ThermoFisher Scientific, https: / / www.fei.com / 25-years-of-dualbeam-innovation / ?utm_source=blog&utm_medium=blog&utm_campaign=25th+DualBeam+blog&utm_content=blog). A Ga ion beam is used with a voltage of 30 kV and a current of 30 pA to 7 nA. The etched sample has dimensions of 5 × 8 μm and a thickness of 100 nm. Using the prepared samples, the surface characteristics from the surface to the center of the positive electrode active material powder particles are analyzed by TEM and energy-dispersive X-ray spectroscopy (EDS). TEM-EDS line scans were performed on a JEM-2100F (JEOL, https: / / www.jeol.co.jp / en / products / detail / JEM-2100F.html) using X-Max N This is performed using an Oxford Instruments 80T (https: / / nano.oxinst.com / products / x-max / x-max). EDS analysis of the particles provides quantitative elemental analysis of the cross-section.
[0096] Line profiles measured as a function of linear distance in the cross section of the particle are smoothed by a 10-point Savitzhky-Golay filter using Origin 9.1 software to reduce the analytical errors inherent in EDS.
[0097] The TEM-EDS line profiling analysis of all elements, expressed as atomic % of the total amount of Ni, Mn, Co, B, Mg, Al, Nb, Ti, W and Zr, is illustrated, for example, in FIG.
[0098] 1.8.Particle size distribution The particle size distribution (PSD) of the positive electrode active material powders is measured by dispersing each of the powder samples in an aqueous medium and then using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpanalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview). Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurement.
[0099] 1.9. Polymer cell test 1.9.1. Preparation of polymer cells 1.9.1.1. Preparation of Solid Polymer Electrolyte (SPE) A solid polymer electrolyte (SPE) is prepared according to the following method. Step 1) Polyethylene oxide (PEO) (PEO with a molecular weight of 1,000,000, Alfa Aesar, https: / / www.alfa.co.kr / AlfaAesarApp / faces / adf.task-flow?adf.tfId=ProductDetailsTF&adf.tfDoc= / WEB-INF / ProductDetailsTF.xml&ProductId=043678&_afrLoop=1010520209597576&_afrWindowMode=0&_afrWindowId=null) was dissolved in 99.8 wt% anhydrous acetonitrile (Aldrich, https: / / www.sigmaaldrich.com / catalog / product / sial / 271004?lang=ko®ion=KR&gclid=EAIaIQobChMIwcrB0dDL6AIVBbeWCh0ieAXREAAYASAAEgJCa_D_BwE) to prepare lithium bis(trifluoromethanesulfonyl)imide salt (LiTFSI, Soulbrain Co., Ltd.) using a mixer for 30 minutes at 2000 revolutions per minute (rpm). The molar ratio of ethylene oxide to lithium is 20. Step 2) Pour the mixture from step 1) into a Teflon dish and dry at 25°C for 12 hours. Step 3) Remove the dried SPE from the dish and punch out the dried SPE to obtain an SPE disk with a thickness of 300 μm and a diameter of 19 mm.
[0100] 1.9.1.2. Preparation of the Catholyte Electrode The catholyte electrode is prepared according to the following method. Step 1) Prepare a polymer electrolyte mixture containing a solution of polycaprolactone (PCL) (PCL with a molecular weight of 80,000, Sigma-Aldrich, https: / / www.sigmaaldrich.com / catalog / product / aldrich / 440744) in 99.7 wt% anhydrous anisole (Sigma-Aldrich, https: / / www.sigmaaldrich.com / catalog / product / sial / 296295) and bis(trifluoromethanesulfonyl)imide salt (LiTFSI, Sigma-Aldrich, https: / / www.sigmaaldrich.com / catalog / product / aldrich / 544094) in acetonitrile. The mixture has a weight ratio of PCL:LiTFSI of 74:26. Step 2) The polymer electrolyte mixture prepared in step 1), the positive electrode active material, and the conductor powder (Super P, Timcal (Imerys Graphite & Carbon), http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2018 / 10 / ENSACO-150-210-240-250-260-350-360-G-ENSACO-150-250-P-SUPER-P-SUPER-P-Li-C-NERGY-SUPER-C-45-65-T_V-2.2_-USA-SDS.pdf) are mixed in an acetonitrile solution in a weight ratio of 21:75:4 to prepare a slurry mixture. Mixing is performed by a homogenizer at 5000 rpm for 45 minutes. Step 3) Cast the slurry mixture from step 2) onto one side of a 20 μm thick aluminum foil with a coater gap of 100 μm. Step 4) The slurry-cast foil is dried at 30° C. for 12 hours and then punched out to obtain catholyte electrodes with a diameter of 14 mm.
[0101] 1.9.1.3. Polymer cell assembly Assemble a coin-shaped polymer cell in an argon-filled glove box in the following order from bottom to top: 2032 coin cell can, catholyte electrode prepared in section 1.9.1.2, SPE prepared in section 1.9.1.1, gasket, Li anode, spacer, wave spring, and cell cap. The coin cell is then completely sealed to prevent electrolyte leakage.
[0102] Test Method Each coin-shaped polymer cell is cycled at 80 °C using a Toscat-3100 computer-controlled constant current cycling station (Toyo Systems, http: / / www.toyosystem.com / image / menu3 / toscat / TOSCAT-3100.pdf). The coin cell test procedure uses a 1C current definition of 160 mA / g in the 4.4-3.0 V / Li metal window range according to the following schedule: Step 1) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V, followed by a 10 minute rest. Step 2) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0 V, followed by a 10 minute rest. Step 3) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V. Step 4) Switch to constant voltage mode and maintain 4.4V for 60 hours. Step 5) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0V.
[0103] Q total Q is defined as the total leakage capacity at high voltage and temperature in step 4 of the described test method. total A small value of indicates that the positive electrode active material powder has high stability during high temperature operation.
[0104] 2. Examples and Comparative Examples Comparative Example 1 General formula Li 1.01 (Ni 0.63 Mn 0.22 Co0.15 ) 0.99 A single crystal positive electrode active material having O2, designated as CEX1, is obtained through a solid-state reaction between a lithium source and a nickel-based transition metal source. The method is carried out as follows: Step 1) Preparation of transition metal hydroxide precursor: Metal composition Ni 0.63 Mn 0.22 Co 0.15 A nickel-based transition metal hydroxide powder (TMH1) having a median particle size (D50) of 1.0 μm and 5.8 μm is prepared by co-precipitation in a large-scale continuous stirred tank reactor (CSTR) with mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia. Step 2) First Mixing: TMH1 prepared in step 1) is mixed with Li2CO3 in an industrial blender to obtain a first mixture with a lithium to metal (Li / Me) ratio of 0.85. Step 3) First calcination: The first mixture from step 2) is calcined at 900° C. for 10.3 hours in a dry air atmosphere to obtain a first calcined cake, which is a first intermediate product. Step 4) Second mixing: The first intermediate product from step 3) is mixed with LiOH in an industrial blender to obtain a second mixture with a lithium to metal (Li / Me) ratio of 1.050. Step 5) Second calcination: The second mixture from step 4) is calcined at 950°C for 10.25 hours in dry air, followed by wet bead milling, drying and sieving methods to obtain the second calcined powder, the second intermediate product. Step 6) Third mixing: The second intermediate product from step 5) is mixed with 1.5 mol% LiOH with respect to the total molar content of Ni, Mn and Co in the second intermediate product in an industrial blender to obtain a third mixture. Step 7) Third firing: The third mixture from step 6) is sintered at 750° C. for 10 hours in dry air to produce CEX1 with a Li / Me ratio of 1.02.
[0105] In particular, wet bead milling is believed to be involved in obtaining a single crystal morphology.
[0106] Example 1 A single crystalline positive electrode active material EX1.1 is prepared according to the following method. Step 1) Slurry preparation: Place 100 grams of deionized water in a beaker on a hot plate. Once the temperature of the deionized water is 60°C, add 100 grams of CEX1 to the deionized water to prepare the first slurry. Step 2) Addition of cation and anion precursors: The first slurry is stirred at 600 rpm by a magnetic stirrer. After the first slurry reaches a stable temperature of 60°C, 0.5 mol% of the cation precursor CoSO4 and 0.5 mol% of the anion precursor Na2WO4 solution relative to the total molar content of Ni, Mn, and Co of CEX1 are injected into the beaker to prepare the second slurry. The second slurry is stirred continuously for 10 minutes. Step 3) Filtration and drying: After 10 minutes, the powdered coated lithium transition metal oxide particles are separated from the liquid by filtration. The isolated particles are rinsed with 50 mL of deionized water and dried. Step 4) Heating: The dried isolated microparticles are then heated at 375° C. for 10 hours under a dry air atmosphere and designated as EX1.1.
[0107] EX1.2 is prepared following the same method as EX1, except that the amounts of cation and anion precursors added in step 2 are 1.0 mol % each.
[0108] EX1.3 is prepared following the same method as EX1, except that the heating temperature is 450°C instead of 375°C.
[0109] Example 2 EX2.1 is prepared according to the same method as EX1.1, except that the cation and anion precursors added in step 2 are MnSO4 and Na2WO4, respectively.
[0110] Comparative Example 2 CEX1 is heated at 375°C for 10 hours under a dry air atmosphere. 100 grams of the resulting product is mixed with 100 grams of deionized water at a temperature of 60°C to prepare a first slurry. The first slurry is stirred for 10 minutes at 600 rpm (revolutions per minute) by a magnetic stirrer. After 10 minutes, the powder is separated from the liquid by filtration. The separated powder is dried. The dried powder is finally heated at 375°C for 10 hours under a dry air atmosphere and is called CEX2.1.
[0111] CEX2.2 is prepared following the same method as EX2.1, except that the heating temperature in step 4 is 250°C.
[0112] Example 3 EX3.1 is prepared according to the same method as EX1.1, except that the anionic compound added in step 2 is NaAlO2.
[0113] EX3.2 is prepared in the same manner as EX3.1, except that the heating temperature in step 4 is 750°C.
[0114] Examples 4 to 8 EX4-EX8 are prepared according to the same method as EX1.1, except that the cation and anion precursors added in step 2 are according to Table 3.
[0115] Comparative Examples 3 and 4 CEX3 and CEX4 are prepared following the same method as EX1.1, except that the cation and anion precursors added in step 2 are according to Table 3.
[0116] EX1 to EX8 and CEX2 to CEX4 have a Li / Me ratio of about 1.01.
[0117] [Table 4]
[0118] *: Molar content of each compound added in step 2 from the preparation of EX1.1. ** : Heating temperature applied in step 4 from the preparation of EX1.1. *** :Not applicable.
[0119] FIG. 1A shows an SEM image of CEX1 having a single crystal morphology.
[0120] Figure 1B shows an SEM image of EX1.1. Small particles are present on the surface of the larger particles, which are absent in CEX1. It is easy to see that EX1.1 is single crystalline. The area marked 100 represents the Co-rich outer layer. The secondary particles marked 200 are believed to be formed mainly by the phase Li6W2O9, as shown by the XRD analysis in Figure 2.
[0121] Figure 2 shows the X-ray diffraction patterns of CEX1 and EX1.1. Two phases are identified in the EX1.1 diffractogram: the R-3m phase, which is Li 1+a (Ni 0.63 Mn 0.22 Co 0.15 ) 1-a The Pm3m phase corresponds to Li6W2O9, and the Pm3m phase corresponds to Li6W2O9. The Li6W2O9 is formed in the method for producing a positive electrode active material according to the present invention. The presence of the Pm3m phase in XRD is indicated by, for example, diffraction peaks at 2θ of 23.8±0.1°, 26.2±0.1°, 30.3±0.1°, and 32.2±0.1°.
[0122] In the XRD results of comparative example CEX1, the phase Li6W2O9 is not observed.
[0123] Table 3 shows the method parameters and the Q of the obtained positive electrode active material. total EX1 has a Q of 60.03mAh / g. total A lower Q of 45 mAh / g compared to bare CEX1 total Similarly, EX1.2 is observed to have a Q of 31.40 mAh / g. total has.
[0124] Treatment in a slurry of MnSO4 and Na2WO4 and heating the coated microparticles to a temperature of 250°C resulted in a Q of 62.87 mAh / g, as shown in CEX2.2. total Heat treatment at temperatures above 300° C., e.g., 375° C. in EX2.1, results in a cathode active material having a significantly reduced Q total , i.e., a Q of 43.86 mAh / g total This shows the Q of EX1.1. total This is a value comparable to
[0125] EX3.1 and EX3.2 introduce CoSO4 and NaAlO2 as the cation and anion precursors, respectively, at different heating temperatures. EX3.1 heated at 375°C has a Q of 31.92 mAh / g. total EX3.2 heated at 750°C had a Q of 37.93mAh / g. total It can be concluded that any temperature condition is suitable for this method.
[0126] Other combinations of cation precursors and anion precursors are applied in EX4-EX8, CEX3, and CEX4, as listed in Table 3. The results in Table 3 demonstrate that the positive electrode active material prepared by the method according to the present invention has better stability at high temperature and high voltage application.
[0127] A possible mechanism is that the reaction of the anion and cation precursors produces a protective layer to prevent the metal dissolution process from the positive electrode active material at high temperature and high voltage application.
[0128] The particle size distribution of EX1.1 and EX1.3 was determined, which showed that EX1.1 and EX1.3 had a median particle size D50 of 7 μm.
[0129] Coin cell tests were performed with CEX1, CEX2.1, EX1.1 and EX1.3 as described above.
[0130] Table 4 contains a summary of the relevant results.
[0131] [Table 5]
[0132] The reaction for the surface treatment of EX1.1 is represented by the formula CoSO 4(aq) +Na2WO 4(aq) →CoWO 4(s) +NaSO 4(aq) It is presumed that CoWO4 precipitates on the surface of the positive electrode active material. The Li6W2O9 secondary phase (200) according to the present invention as shown in FIG. 1B can be obtained by the following heat treatment of the positive electrode active material containing the CoWO4 compound on its surface.
[0133] CO over 1.00 XPS / CO ICP This ratio demonstrates that the surface region of the particles in the examples is enriched with respect to cobalt.
[0134] With regard to the electrochemical properties, there is believed to be a synergistic effect between the enrichment of Co at the surface of the particles and the presence of a secondary Li6W2O9 phase.
[0135] FIG. 4 shows the full cell cycle performance of EX1.1 and CEX1. The cycle life is defined as the number of charge-discharge cycles before the discharge capacity drops to the initial discharge capacity or below 80% of it. The cycle life values are obtained from the extrapolation of the linear equation. It is clear that EX1.1 has a smaller slope and reaches 80% capacity after 2155 cycles. The cycle life of CEX1 is 1462 cycles, which is shorter than that of EX1.1. The full cell specific capacity (SQ) of EX1.1 and CEX1 is 167.1mAh / g and 164.7mAh / g, respectively, indicating the superiority of EX1.1 in the context of the present invention.
[0136] FIG. 3 shows the TEM-EDS line profiling of the cross section of EX1.1, made by SEM-FIB. The main element of the outermost layer is tungsten, which is from the Li6W2O9 secondary phase (200) according to FIG. 1. The thickness of the secondary phase (200) is approximately 60 nm. A Co-rich layer with a thickness of approximately 50 nm is shown from the bottom of the secondary phase (200). It is important to note that the thickness may vary according to the grain and site selection and measurement direction.
Claims
1. A method for producing a positive electrode active material for a solid state rechargeable battery comprising Li, O and M, wherein M is Co with a content x of 0 mol% or more and 35.00 mol% or less; Mn having a content y of 0 mol% or more and 35.00 mol% or less; A having a content z of 0 mol% or more and 10.00 mol% or less, which is at least one element selected from B, Mg, Al, Nb, Ti, W, Y, Ca, S, P, Sn, Si and Zr; and Ni with a content of 100.00 mol%-x-y-z It consists of: The contents x, y and z are relative to M and are determined by ICP, and the method comprises the steps of: Step 1: preparing a slurry, the slurry comprising a liquid and a lithium mixed metal oxide powder, the lithium mixed metal oxide powder being: Li, O and Q, where Q is Co with a content a of 0 mol% or more and 35.00 mol% or less; Mn having a content b of 0 mol% or more and 35.00 mol% or less; G, which has a content c of 0 mol% or more and 10.00 mol% or less, and which is at least one element selected from B, Mg, Al, Nb, Ti, W, Y, Ca, S, P, Sn, Si and Zr; and Ni with a content of 100.00 mol%-a-b-c It consists of: The contents a, b and c are relative to Q and are determined by ICP; Step 2: The lithium mixed metal oxide powder is treated with Al before and / or after and / or during step 1. 3+ , La 3+ , Co 2+ , Co 3+ , Mn 2+ , Mn 3+ , Mn 4+ , Mn 6+ , Zn 2+ , Cu + , Cu 2+ , Mg 2+ and a cation precursor comprising at least one cation selected from the general formula A′ y’ O z’ -x’ with an anion precursor comprising at least one anion having the formula: A′ is selected from B, Al, Sn, Si, P, W, and 0.5≦x′≦4, 0.5≦y′≦2, and 1≦z′≦12; Step 3: Optionally, filtering and optionally drying the slurry to obtain a wet or dry solid; and Step 4: Heating the slurry from steps 1 and 2 or the solid from step 3 at a temperature in the range of 300° C. to 1000° C.; A method comprising:
2. The method of claim 1 , wherein a is 5.0 mole percent or greater.
3. 10. The method of claim 1, wherein the lithium mixed metal oxide powder is a plurality of single crystal particles.
4. 2. The method of claim 1, wherein the active cathode material has a Li / (Ni+Co+Mn) molar ratio greater than or equal to 0.90 and less than or equal to 1.10, and the lithium mixed metal oxide powder has a Li / (Ni+Co+Mn) molar ratio greater than or equal to 0.90 and less than or equal to 1.
10.
5. The method of claim 1 , wherein the liquid is water and the cation precursors and the anion precursors are soluble in the liquid.
6. 2. The method of claim 1 , wherein the active cathode material comprises a phase corresponding to a crystalline salt of lithium ions and the anion as determined by XRD.
7. The method of claim 1 , wherein A′ is an element W.
8. The cation precursor is Co 2+ and / or Co 3+ The method of claim 7, comprising:
9. The positive electrode active material has a Li 6 W 2 O 9 The method of claim 7 or 8, comprising:
10. 2. The method of claim 1, wherein x≦15.00 mol % and y≦5.00 mol %, A comprises Al, and M has an Al content of 1.00 mol % or greater.
11. 2. The method of claim 1, wherein z≦5.00 mol % and 10.00 mol %≦y.
12. 2. The method of claim 1, wherein 15.00 mol%≦x≦30.00 mol%, and 15.00 mol%≦y≦30.00 mol%, and z≦3.00 mol%.
13. A positive electrode active material for a rechargeable solid-state battery, the positive electrode active material being a powder, The positive electrode active material has a Co content of Co A , Ni content Ni A , and Mn content Mn A and Co A , Ni A and Mn A was determined by ICP analysis, and A , Ni A and Mn A is expressed as a mole fraction, and the positive electrode active material is Co A / (Co A + Ni A + Mn A ) with a value A defined as The positive electrode active material has an average Co fraction of Co B , average Ni fraction Ni B and the average Mn fraction Mn B indicates, Co B , Ni B and Mn B is expressed as a mole fraction, and the positive electrode active material is Co B / (Co B + Ni B + Mn B ) with a value B defined as The positive electrode active material has a Li x W y O z phase, 1.0≦x≦8.0, 1.0≦y≦5.0, 3.0≦z≦10.0; The ratio B / A is at least 1.
25.
14. The positive electrode active material has a Li content, Li, determined by ICP and expressed as a mole fraction. A and Li A / (Co A + Ni A + Mn A 14. The cathode active material of claim 13, wherein m is at least 0.81 and at most 1.21, or greater than 0.
95.
15. Ni A / (Co A + Ni A + Mn A 14. The cathode active material of claim 13, wherein R(x,y) is at least 0.35, or at least 0.
55.
16. Co A / (Co A + Ni A + Mn A 16. The cathode active material of claim 15, wherein m is at least 0.02 and at most 0.
40.
17. The powder is a plurality of particles, and the Li x W y O z 14. The active cathode material of claim 13, wherein the phase is present on the surface of the particles as determined by XRD and TEM / EDS line profiling produced by SEM-FIB.
18. The powder is a plurality of particles, and the Li x W y O z 14. The cathode active material of claim 13, wherein the phase exists as secondary particles on the surface of the particles.
19. The Li x W y O z The phase is Li as determined by XRD. 6 W 2 O 9 The positive electrode active material according to claim 13 .
20. The positive electrode active material is Co A and Ni A and Mn A 14. The cathode active material of claim 13 having a W content that is at least 0.1 mol % of the sum of
21. The positive electrode active material is Co A and Ni A and Mn A or Co A and Ni A and Mn A 14. The cathode active material of claim 13 having a W content that is at most 1.0 mol % of the sum of
22. The cathode active material of claim 13 , wherein the powder is a single crystal powder.
23. 14. The cathode active material of claim 13, wherein the powder has a particle size distribution determined by laser diffraction, the particle size distribution having a median particle size D50 that is at least 1.0 μm and at most 15 μm.
24. The positive electrode active material has a content X of one or more elements X. A X is one or more of B, Mg, Al, Nb, Ti, and Zr; A is determined by ICP, and X A is expressed as a mole fraction, Mn A / (Co A + Ni A + Mn A ) is at least 0.10 and at most 0.60, and Co A / (Co A + Ni A + Mn A ) is at least 0.02 and at most 0.40; X A / (Co A + Ni A + Mn A ) is at most 0.10 and is equal to or greater than 0, A / (Co A + Ni A + Mn A 14. The cathode active material of claim 13, wherein n is at most 0.88.
Citation Information
Patent Citations
Lithium-ion secondary battery
JP2006351379A
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery including the positive electrode active material
JP2013125732A
Positive electrode active material for secondary battery, method for producing the same, and secondary battery including the same
JP2018515884A
Positive electrode active material for secondary battery and secondary battery containing the same
JP2018532236A
Positive electrode active material for secondary battery, and secondary battery including the same
JP2018534734A